PENGOLAHAN JAGUNG SEBAGAI UPAYA PENINGKATAN PENGHASILAN MASYARAKAT MELALUI KRUPUK SEBAGAI IDE KREATIF DI DESA TANGKULOWI KECAMATAN KULAWI - Irmawati; Rukhayati; Rangga Saputra (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
Maize is one of the main agricultural commodities in Indonesia, especially in rural areas. Most people still utilize maize only as staple food or animal feed. Therefore, innovations in corn processing are needed to increase community income through value-added products. One creative idea that can be developed is the processing of corn into chips. Corn chips are processed products that have good market potential, because in addition to being nutritious, they also have a crunchy texture and taste that can be adjusted to consumer preferences This community service program aims to: 1.Develop community skills in processing corn into chips.2.Increase the economic value of corn through product diversification.3.Open new business opportunities for village communities.4.Increase community income through marketing corn chips products.Methods used in this study, a) Socialization and Education, b) Technical training in processing corn chips, c) Packaging and marketing assistance, d) Monitoring and Evaluation. Processing corn into chips is one of the creative solutions in increasing the added value of local agricultural commodities. By providing training and assistance to the community, it is hoped that they can develop this business as an additional source of income that can sustain the village economy.